Delirium screening instruments administered by nurses for hospitalized patients - literature review - Blažena Ševčíková; Hana Matějovská Kubešová; Lenka Šáteková; Elena Gurková (University of Ostrava, 2019)
Aim: The aim of the paper was to create a literature review of valid and reliable delirium screening instruments administered by nurses for hospitalized patients. Design: Literature review. Methods: An advanced search of three licensed electronic databases (EBSCO, MEDLINE, PROQUEST) was selected. Twenty-one research studies complied with the inclusion criteria. Results: The predictive validity of ten delirium screening measuring tools were studied. The best predictive validity was found in the Nursing Delirium Screening Scale (Nu-DESC), with sensitivity values ranging from 32% to 100%, and specificity from 83% to 100%, with highest value for reliability of 0.94. The Delirium Observation Screening Scale (DOS) came second, with sensitivity from 25% to 97%, and specificity from 89% to 98.4%, with highest value for reliability of 0.77. The 4AT tool had sensitivity values from 83.3% to 90%, and specificity from 84% to 86.3%, with highest value for reliability of 0.99. Conclusion: The best screening tool for evaluating delirium by nurses was the Nu-DESC, followed by the DOS, and the 4AT. We recommend testing the predictive validity and reliability of selected screening tools administered by nurses in conditions of Czech clinical practice.